Cytokine expression during early and late phase of acute Puumala hantavirus infection - Sadeghi, Mahmoud (BioMed Central, 2011)
BACKGROUND: Hantaviruses of the family Bunyaviridae are emerging zoonotic pathogens which cause hemorrhagic fever with renal syndrome (HFRS) in the Old World and hantavirus pulmonary syndrome (HPS) in the New World. An immune-mediated pathogenesis is discussed for both syndromes. The aim of our study was to investigate cytokine expression during the course of acute Puumala hantavirus infection. RESULTS: We retrospectively studied 64 patients hospitalised with acute Puumala hantavirus infection in 2010 during a hantavirus epidemic in Germany. Hantavirus infection was confirmed by positive anti-hantavirus IgG/IgM. Cytokine expression of IL-2, IL-5, IL-6, IL-8, IL-10, IFN-γ, TNF-α and TGF-β1 was analysed by ELISA during the early and late phase of acute hantavirus infection (average 6 and 12 days after onset of symptoms, respectively). A detailed description of the demographic and clinical presentation of severe hantavirus infection requiring hospitalization during the 2010 hantavirus epidemic in Germany is given. Acute hantavirus infection was characterized by significantly elevated levels of IL-2, IL-6, IL-8, TGF-β1 and TNF-α in both early and late phase compared to healthy controls. From early to late phase of disease, IL-6, IL-10 and TNF-α significantly decreased whereas TGF-β1 levels increased. Disease severity characterized by elevated creatinine and low platelet counts was correlated with high pro-inflammatory IL-6 and TNF-α but low immunosuppressive TGF-β1 levels and vice versa . CONCLUSION: High expression of cytokines activating T-lymphocytes, monocytes and macrophages in the early phase of disease supports the hypothesis of an immune-mediated pathogenesis. In the late phase of disease, immunosuppressive TGF-β1 level increase significantly. We suggest that delayed induction of a protective immune mechanism to downregulate a massive early pro-inflammatory immune response might contribute to the pathologies characteristic of human hantavirus infection.